Biological and structural properties of curcumin-loaded graphene oxide incorporated collagen as composite scaffold for bone regeneration - Xie, Qi; Wang, Tianqi; He, Lina; Liang, Hongbo; Sun, Jingxuan; Huang, Xiaoxiao; Xie, Weili; Niu, Yumei (Frontiers in Bioengineering and Biotechnology, 2024)
To address the challenges related to bone defects, including osteoinductivity deficiency and postimplantation infection risk, this study developed the collagen composite scaffolds (CUR-GO-COL) with multifunctionality by integrating the curcumin-loaded graphene oxide with collagen through a freeze-drying-cross-linking process. Their morphological and structural characteristics were analyzed, as well as the physicochemical properties, including water absorption, water retention and porosity. The CUR-GO-COL composite scaffold with a CUR-GO concentration of 0.05% (w/v) exhibits optimal biological compatibility and stable and slow curcumin release rate. Furthermore, in vitro cell and bacterial tests demonstrated that the prepared CUR-GO-COL composite scaffolds enhance cell viability, proliferation and adhesion, and offer superior osteogenic and antimicrobial properties compared with the CUR-GO composite scaffold, confirming the osteogenesis promotion and antimicrobial effects. Therefore, the introduction of CUR-GO into collagen scaffold creates a bonefriendly microenvironment, and offers a theoretical foundation for the design, investigation and utilization of multifunctional bone tissue biomaterials.